If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(q-2)+2=8q-6-2q
We move all terms to the left:
4(q-2)+2-(8q-6-2q)=0
We add all the numbers together, and all the variables
4(q-2)-(6q-6)+2=0
We multiply parentheses
4q-(6q-6)-8+2=0
We get rid of parentheses
4q-6q+6-8+2=0
We add all the numbers together, and all the variables
-2q=0
q=0/-2
q=0
| 16+2n=6(7n-4) | | 8+x=13+2× | | 23=u/4+8 | | 5x=45=15 | | 21+13x=85+9x | | 2(2x+4)+2x+10=x | | 7/3x+6=-1 | | 8+5b=-13+2b | | 219+43x=794+18x | | 3,8x-3=3,7 | | 3y+3÷2=15÷2 | | 2+2v=-8-3v | | 13+8x=61+4x | | 3(6x-5)=12x-21 | | 39+13x=199+5x | | -2x+6=-3x-2 | | 5x+3+3x-10=25 | | 15x=11+4 | | 3x-12=88 | | 5-4x=-5+11 | | -x+30=2x+3 | | 5+(3x+1)-5(x+1)=-2 | | 19+7x=31+5x | | h-199=491 | | -12=-6/7v | | 2x−4=254 | | 5(x÷2-4)-3(x+8)=0 | | ^3q+2=^5 | | -1=n/3=-4 | | 20+14x=140+9x | | m×m+m=10 | | 47y=28y |